Reconstructing Glacier Surge Kinematics Using a Numerical Ice‐Flow Model Applied to the Dusty Glacier, St. Elias Mountains, Canada - Erik M. Young; Gwenn E. Flowers; Hester Jiskoot; H. Daniel Gibson (Geophysical Research Letters, 2024)
Abstract Long‐term records of the flow patterns and dynamics of surge‐type glaciers improve our understanding of their underlying dynamic processes, and are critical to better resolve their contribution to a changing cryosphere. We adapt a modeling approach designed to emulate glacier surging and fold kinematics using the full Stokes ice‐flow model Elmer/Ice to simulate surging of the Dusty Glacier, located in the St. Elias Mountains, Canada. We combine distributed mass‐balance and numerical ice‐flow models to reconstruct the fold kinematics of the 2001–2003 surge of the Dusty Glacier by comparing model results to Landsat‐7 and Sentinel‐2 imagery, and assess the sensitivity of centennial‐scale modeled glacier structure to different mass balance and sliding parameterizations. This study demonstrates the feasibility of using the approach to reconstruct the surface structure kinematics of a surge‐type glacier in nature, highlighting its potential application to other surge‐type glaciers and regions.